Better off together: A cluster analysis of self-leadership and its relationship to individual innovation in hospital nurses - Gomes,Catarina (2015)
Self-leadership is designed to influence positive outcomes like individuals innovative capacity in the workplace. Nevertheless, research on the relationship between self-leadership and individual innovation has failed to determine which self-leadership strategies contribute to innovation. Thus, this study aims to: explore the existence of different profiles of self-leadership strategies in hospital nurses and, test if these different profiles have different effects on individuals ability to be innovative. 288 nurses participated in this study. Firstly, data was analysed using Cluster analysis. Secondly, to verify the significance of the association between self-leadership clusters and individual innovation chi-square tests were conducted and the adjusted residuals were considered. Results revealed the existence of 3 different clusters of self-leadership, and that individual innovation is more frequent when all self-leadership strategies are used. The findings suggest that self-leadership strategies vary between individuals and that they all should be fostered in order to promote individual innovation.